High-Resolution Optical Ifu Spectroscopy of the Complex Galaxy Merger Ii Zw 096 - Olivares-Sepulveda, V (IOP Publishing Ltd, 2025)
Luminous and ultraluminous IR galaxies are critical for investigating feedback mechanisms due to a combination of intense star formation episodes and active galactic nuclei (AGN), particularly in the context of complex galaxy interactions. We conduct a detailed analysis of the II ZW 096 merging system using the Multi-Unit Spectroscopic Explorer on the Very Large Telescope, combining high-resolution narrow-field mode and large-area wide-field mode observations. We mapped the morphology, kinematics, and ionizing radiation of the system s gas by fitting atomic emission lines and the optical continuum. We identify three or more distinct galaxies within II ZW 096, revealing rotational patterns and complex interactions consistent with a collapsing small galaxy group. The kinematics and ionization structures suggest high star formation rates and shock-driven processes, which align with this proposed scenario. Focusing on the D1 compact region, which contributes 40%-70% of the system s IR emission, and combining information from archival multiwavelength observations, we find strong evidence of a heavily obscured AGN powering it. Our analysis of the internal structure, interactions, and merger state of II ZW 096 offers novel insights into the galaxy evolution processes in this dynamic and highly chaotic system.